2021
DOI: 10.1371/journal.pone.0250747
|View full text |Cite
|
Sign up to set email alerts
|

Glycans unique to the relapse-prone subset within triple-negative breast cancer as revealed by lectin array-based analysis of surgical specimens

Abstract: Introduction Molecular and cellular characteristics of the relapse-prone subset within triple-negative breast cancer (TNBC) remain unclear. Aberrant glycosylation is involved in the malignant behavior of cancer cells. In the present study, we aimed to reveal glycan profiles unique to relapsed TNBC patients. Methods Thirty TNBC patients who did not undergo neoadjuvant chemotherapy but postoperative standard adjuvant therapy from 2009 through 2016 at Juntendo Hospital were investigated. TNBC cells were resecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Furthermore, dramatic changes were observed in protein glycosylation levels in gastrointestinal track tumors (esophageal, gastric, and colorectal cancers), thereby generating molecular fingerprints (Fernandes et al, 2020). Similar tumor-specific glycosylation findings were also identified in ovarian, cervical, and breast carcinoma (Hu et al, 2020;Sakata-Matsuzawa et al, 2021;Lopes et al, 2021;Xu et al, 2021).…”
Section: Cancer and Glycosylationmentioning
confidence: 64%
“…Furthermore, dramatic changes were observed in protein glycosylation levels in gastrointestinal track tumors (esophageal, gastric, and colorectal cancers), thereby generating molecular fingerprints (Fernandes et al, 2020). Similar tumor-specific glycosylation findings were also identified in ovarian, cervical, and breast carcinoma (Hu et al, 2020;Sakata-Matsuzawa et al, 2021;Lopes et al, 2021;Xu et al, 2021).…”
Section: Cancer and Glycosylationmentioning
confidence: 64%
“…Most of these previous studies have focused on the changes in WFA binding in serum samples; few studies have focused on WFA binding to cell surface molecules [ 29 ]. We previously reported that surgical specimens of relapsed triple-negative breast cancer patients showed higher levels of WFA binding than that of non-relapsed groups, using lectin microarrays [ 29 ]. In the present study, we identified WFA as a lectin having differential binding between TAM-resistant and sensitive breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“… The curve shown in red represents recurrence-free-survival of patients with B3GALNT2 mRNA-high tumors, while the black curve shows those with low B3GALNT2 tumors. The data was obtained from publicly available Kaplan–Meier plotter mRNA microarray databases [ 29 ]. …”
Section: Supporting Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Further bioinformatic analyses are necessary to identify the potential links, key pathways and targets of these proteins. Second, the data obtained from protein microarrays need to be further Lectin microarray Triple-negative breast cancer Discovery of biomarkers for monitoring the efficacy of treatment [100] Lectin microarray Colorectal cancer Detection of biomarkers for early diagnosis [101] Lectin microarray Thyroid cancer Discovery of biomarkers for prognostic assessment [102] coworkers [106] reported that surface-attached hydrogel networks may be a promising strategy for achieving highly sensitive and quantitatively reproducible microarrays. In addition, it is worth mentioning that Schroder et al [107] adopted a dual-colour labelling strategy inspired by DNA microarrays to reduce the systemic errors caused by the monochromatic tagging pattern.…”
Section: Perspectivesmentioning
confidence: 99%